2008
DOI: 10.1007/s00705-008-0196-5
|View full text |Cite
|
Sign up to set email alerts
|

The low-virulent African swine fever virus (ASFV/NH/P68) induces enhanced expression and production of relevant regulatory cytokines (IFNα, TNFα and IL12p40) on porcine macrophages in comparison to the highly virulent ASFV/L60

Abstract: The impact of infection by the low-virulent ASFV/NH/P68 (NHV) and the highly virulent ASFV/L60 (L60) isolates on porcine macrophages was assessed through the quantification of IFNα, TNFα, IL12p40, TGFβ and ASFV genes by real-time PCR at 2, 4 and 6 h post-infection. Increased IFNα, TNFα and IL12p40 expression was found in infection with NHV, in which expression of TGFβ was lower than in infection with L60. Principal component analysis showed a positive interaction of cytokines involved in cellular immune mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
60
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 31 publications
10
60
2
Order By: Relevance
“…This was confirmed in macrophages infected with L60 and NHV, where higher levels of IFNa were produced in the early stages of infection with NHV than with L60, in addition to other cytokines involved in inflammatory responses and cellular immunity (Gil et al, 2008). Pr4D35 is also attenuated in swine (Afonso et al, 2004).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This was confirmed in macrophages infected with L60 and NHV, where higher levels of IFNa were produced in the early stages of infection with NHV than with L60, in addition to other cytokines involved in inflammatory responses and cellular immunity (Gil et al, 2008). Pr4D35 is also attenuated in swine (Afonso et al, 2004).…”
Section: Discussionmentioning
confidence: 72%
“…When the same stretch of genes, and 3NR (MGF 505-2R/A489R), were deleted from Pretorisuskop/96/4 (Pr4D35), growth in macrophages was impaired (Zsak et al, 2001). The same ORFs are absent or truncated in the NHV genome, with even additional genes adjacent to this area deleted or truncated, yet this strain replicates effectively in swine macrophages (Gil et al, 2008;Keil et al, 2014). Further genomic factors have to be contemplated.…”
Section: Discussionmentioning
confidence: 99%
“…There is no available vaccine for ASF (Karalyan et al, 2012). Montgomery was the first to describe ASF, found in Kenya in 1921 (Gil et al, 2008). The virus spread from infected warthogs to domesticated pigs, causing disease with 100% mortality (Jezewska et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…ASFV is a large, icosahedral, double-stranded DNA virus which replicates in infected cells and is classified as the only member of a new virus family, the Asfarviridae (34). ASFV preferentially infects pig monocytes and macrophages which are the main targets for in vivo viral replication (13). The response of macrophages to ASFV infection is critical to understanding the mechanisms of virus pathogenesis and immune evasion.…”
mentioning
confidence: 99%
“…Using the ASFV/NH/P68 (NHV) and the highly virulent ASFV/L60 (L60) model of infection of porcine blood-derived macrophages, Gil et al (13) demonstrated significantly increased production of mRNA for TNFα, IL6, IL12, and IL15 at 6 h pi. Interferon family (IFNs) as one of the most important multifunctional immunoregulatory proteins of inducible cytokines that influence the early or innate immune response to limit viral replication via engagement with their respective IFN receptor is poorly examined with regards to the impact of ASFV infection.…”
mentioning
confidence: 99%